STATISTICAL ASSESSMENT OF BIOMETRICAL SIGNS BY ELECTROCARDIOGRAPHY - M. A. Bogdanov; V. M. Kartak; A. А. Dumchikov; A. I. Fabarisova (Российский кардиологический журнал)
Statistical analysis performed, of the informativity of biometric signs of electrocardiogram. It was found that amplitude and time parameters of PQST areas of electrocardiograms show enough dispersion and are not easily distinguished. For reliable biometric personality identification quite a range of such signs is needed. Based on the known signs, novel signs were formulated via the bootstrap method. The novel signs presented much lower dispersion. It was found, that reliable identification of personality is possible with combined usage of the amplitudes in Sand T-areas of cardiocycle.